PEMANFAATAN LINGKUNGAN DALAM PEMBELAJARAN IPS DI SDN 1 PASAR BARU PAGATAN TANAH BUMBU - Driyan Ngestining (JURNAL SOCIUS, 2014)
This study aimed to describe (1) the learning process with the use of the environment in social studies learning, (2) the performance of teachers in the use of the environment as a source of learning in social studies learning, and (3) barriers and difficulties of teachers in the use of the environment as a source of teaching and learning IPS SDN 1 Pasar Baru Pagatan Tanah Bumbu. The approach in this research is using qualitative descriptive method. The data obtained in this study is derived from information provided by a social studies teacher at the data in the form of primary and secondary data. The technique of collecting data through interviews, observation, and documentation. The results showed that (1) the learning done outside the classroom by making field trips to several places around the school in accordance with the substance of the material to be taught, (2) teachers in the utilization of the environment as the source is through the use of various strategies and methods of learning, such as assignments, field trips, question and answer, and discussion groups so as to create an atmosphere of learning more meaningful, (3) the constraints and difficulties of teachers in the use environment as a learning resource in teaching social studies at SDN 1 New Market Pagatan Tanah Bumbu include limited time, required effort and significant costs while doing filed trip, as well as the lack of support the community around the school.Keywords: Use of Environmental, Social Learning